2021
DOI: 10.1186/s43088-021-00142-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isolated Bacillus ureolytic bacteria in improving the bio-healing of concrete cracks

Abstract: Background Reinforcement corrosion and the concrete strength reduction are critical problems that resulted from crack creation in concrete. Very expensive and hazardous technologies based on chemical materials have been provided for repairing the cracks. Recently, crack repair using bio-catalysis precipitating bacteria has been developed as a viable and ecofriendly alternative technique. The main target of this study was to select and identify bacterial isolates with high urease activity to use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…For the bacterial spores harvesting, the bacterial isolate was cultured for 24 h in alkaline nutrient broth (D (+)-glucose, 1 g/L, peptone, 15 g/L, sodium chloride, 6 g/L, yeast extract, 3 g/L, and then adding NaOH solution droplets until pH 14). The amended spore concentration in samples was 1.3 × 10 7 spore/cm 3 of the entire concrete mixture 18 . The nutrients, including 40 g/L calcium chloride anhydrous, 65 g/L urea, and 2 g/L yeast extract were dissolved in sterilized tap water for preparing the bio-based concrete.…”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations
“…For the bacterial spores harvesting, the bacterial isolate was cultured for 24 h in alkaline nutrient broth (D (+)-glucose, 1 g/L, peptone, 15 g/L, sodium chloride, 6 g/L, yeast extract, 3 g/L, and then adding NaOH solution droplets until pH 14). The amended spore concentration in samples was 1.3 × 10 7 spore/cm 3 of the entire concrete mixture 18 . The nutrients, including 40 g/L calcium chloride anhydrous, 65 g/L urea, and 2 g/L yeast extract were dissolved in sterilized tap water for preparing the bio-based concrete.…”
Section: Methodsmentioning
confidence: 89%
“…The procedure of the endospore staining was performed as shown by Mokhtar et al . 18 . Alkali solid medium was prepared by adding NaOH solution droplets until pH = 14 to nutrient agar (NA) (5 g peptone, 3 g beef extract, 8 g sodium chloride, and 15 g agar dissolved 1000 mL distilled water) and the bacterial isolate was cultivated on its surface 18 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in compressive strength caused by the entry of bacteria may occur due to calcite that precipitates on the surface of the microorganism cells and concrete pores. The insignificant increase in compressive strength of the media control specimens alone without spore inoculation indicated that media nutrition had no practical effect on increasing strength [23].…”
Section: Bacillusmentioning
confidence: 95%
“…These external factors are keys of bacteria's metabolism to precipitate CaCO₃ (Figure 2) [36]. The precipitation of CaCO₃ is based on the enzymatic reaction by using urease [23]. According to the research [39], the self-healing ratio resulted 44,71% efficiency of incorporation Jsmartech.ub.ac.id of added bacteria in the concrete.…”
Section: Potential Analysis Of Ureolytic Bacteria Speciesmentioning
confidence: 99%